Can't judge a book by its murder - Lillard, Amy (Poisoned Pen Press, 2019)
As Sugar Springs gears up for its all-class high school reunion, Mississippi bookstore owner Arlo Stanley prepares to launch her largest event: a book-signing with the town's legendary alum and bestselling author, Wally Harrison. That's when Wally is discovered dead outside of Arlo's front door and her best friend is questioned for the crime. When the elderly ladies of Arlo's Friday Night Book Club start to investigate, Arlo has no choice but to follow behind to keep them out of trouble. Yet with Wally's reputation, the suspect list only grows longer- his betrayed wife, his disgruntled assistant, even the local man who holds a grudge from a long-ago accident. Between running interference with the book club and otherwise keeping it all together, Arlo anxiously works to get Chloe out of jail. And amidst it all, her one-time boyfriend-turned-private-eye returns to town, just another distraction while she digs to uncover the truth around Wally's death and just what Sugar Springs secret could have led to his murder.